P761 IFX dose-escalation strategy based on a population PK model in IBD patients with secondary loss of response. (16th January 2018) - Guardiola, J; Rodriguez Alonso, L; Serra, K; Santacana, E; Colom, H; Rodríguez-Moranta, F; Gilabert, P; Arajol, C; Sanchez Pastor, E; Bas, J; Padullés, A; Padullés, N
Abstract: Background: Secondary loss of response occurs in 20–50% of IBD patients treated with IFX. Currently, therapeutic drug monitoring (TDM) is often implemented in this setting, and dose is doubled or treatment interval shortened when IFX trough levels (TL) are considered insufficient. Population pharmacokinetic (PopPK) models developed in IBD can help to optimise IFX dosing according to patient factors influencing IFX PK to target the optimal therapeutic TL. The objective of this study was to assess whether individually tailored IFX dosage using Bayesian prediction based on a developed PopPK for Crohn's disease (CD) results in the achievement of the desired TLin CD and ulcerative colitis (UC) patients. The covariates included in this PopPK model are weight, serum albumin concentration (SAC), antibodies towards IFX (ATI) and immunosuppressive therapy. Methods: Consecutive patients with IBD receiving ongoing IFX treatment and developing secondary failure to IFX and with IFX TL < 3 mg/l were prospectively enrolled. Individual IFX doses needed to achieve target IFX TL between 3 and 7 mg/l were estimated by implementing a previously published PopPK model using the non-linear mixed effects modelling software Nonmem®7.3. TL of IFX and ATI concentrations were measured by using ELISA (Promonitor®) before and after dose escalation. Results: This study included 31 patients with IBD (18 CD, 13 UC) and TL < 3 mg/l. IFX TL before and after dose escalation were 1.4 (0.8) and 4.7 (2.5), respectively ( p <0.001). After dose escalation 17 patients (54.8%) achieved IFX TLs between 3 and 7 mg/l, 8 (25.8%) < 3 mg/l and 6 (19.4%) > 7 mg/l. In the univariate analysis only fecal calprotectin concentration > 350 μg/g was significant associated with IFX TLs < 3 mg/l post dose escalation. Conclusions: PopPK model for CD proposed by Fasanmade et al. can be used as a tool to individualise IFX doses in both CD and UC patients. New PopPK analysis including fecal calprotectin as a measure of the inflammatory burden could potentially help to ensure adequate individualised IFX exposure. Individually tailored dosing is feasible in IBD patients with secondary loss of response to IFX.